Risk factors of social anxiety in patients with essential tremor - Hou, Lijun; Lei, Xiaoguang (Frontiers in Psychiatry, 2023)
Objective: To study the risk factors of social anxiety disorder (SAD) in essential tremor (ET) patients. Methods: Motor, cognition, and social anxiety were evaluated using the Fahn-Tolosa-Marin Tremor Rating Scale, Mini-Mental State Examination, and Liebowitz Social Anxiety Scale (LSAS) for each subject. The potential risk factors of SAD in ET were analyzed using univariate analysis. Results: Eighty ET patients and eighty-five healthy controls completed the evaluation. The LSAS evaluation showed that the prevalence of SAD in the ET group was 48.8%, which was significantly higher than that in controls (48.8% vs. 12.9%, P < 0.001). Female sex (Odds Ratios [OR]=4.959, P=0.014), younger age (OR=4.172, P=0.037), and presence of head tremor (OR=4.707, P=0.025) were risk factors of SAD among ET patients. Conclusion: SAD is prevalent in patients with ET. Risk factors, such as female sex, age, and head tremor, should be considered for the prevention and intervention of SAD in ET patients.